Spanned Sectoral Stock Returns Volatility on the Asset Pricing Conditions: Is there any significance? - Agbatogun, Taofeek Osidero; Ariyibi, Mayowa Ebenezer; Olaiya, Kehinde Isiaq; Folami, Rahmon Abiodun (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025DO - 10.58709/niujss.v11i4.2317, 2025)
The perception of sectoral stock return volatility carries meaningful information, especially for portfolio management, as its heterogeneity and periods of financial stress may alter the relevance of traditional asset pricing conditions. This raises the question of whether incorporating volatility into models improves their performance, particularly in emerging markets where risk dynamics are often unstable.  Against this backdrop, this study analyses sectoral stock returns and their volatility dynamics in the Nigerian Stock Exchange using monthly data from periods before and after the global financial crisis. The study assesses the significance of spanning sectoral return volatility within asset pricing frameworks by evaluating the performance of the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT) through time-series and cross-sectional analyses. The findings indicate that while the CAPM explains expected returns through systematic risk (beta), the APT provides relatively stronger explanatory power when historical data are considered; however, no model consistently dominates across sectors. Incorporating sectoral volatility measures enhances the explanatory power of both models, indicating that volatility contains additional information relevant to asset pricing conditions. These results underscore the significance of time-varying risk and parameter uncertainty in explaining equity betas, and offer implications for sector-based portfolio selection in emerging equity markets. Accordingly, the study recommends that market regulators and policymakers should strengthen risk disclosure frameworks and promote volatility-sensitive pricing mechanisms to improve market efficiency in emerging equity markets. Keywords: Capital Asset Pricing Models, Asset Pricing Theory, Nigerian Stock Exchange, Sectoral Stock Returns, Volatility